Developing Elementary Science Online Learning Content Using Schoology - Risda Amini; Insih Wilujeng; Retno Dwi Suryanti; Usmeldi; Refiona Andika (Postgraduate, University of Mataram, 2025)
The development of science and technology can make students interested in participating in the learning process so that it can increase student competence. The reality in the field is that there are still many teachers who have not used schoolology-based online learning because of a lack of information. Teachers are less creative in developing teaching materials that suit the characteristics of students. This research began when researchers discovered gaps in conditions in the field that teachers were still not using technology enough, so that learning was less varied. The aim of the research is to produce online learning content using Schoology in elementary school science learning that is practical, valid and effective to increase student competence. The research uses the ADDIE model which consists of analyze, design, development, implementation, and evaluation. This research produces online elementary science learning content using schoology. The results of the research show that based on the expert assessment of the material, language and media the learning content developed was declared valid, practical based on the responses of students and teachers, and effective in increasing students' competence.